Effects of water fluoridation on early embryonic development of zebrafish - Wei, Ya-Lan; Lin, Xin-Chen; Liu, Ying-Ying; Lei, Yu-Qing; Zhuang, Xu-Dong; Zhang, Hai-Tao; Wang, Xin-Rui (Ecotoxicology and environmental safety, 2024)
Fluoride has strong electronegativity and exposes diversely in nature. Water fluoridation is the most pervasive form of occurrence, representing a significant threat to human health. In this study, we investigate the morphometric and physiological alterations triggered by fluoride stimulation during the embryogenesis of zebrafish and reveal its putative effects of stage- and/or dose-dependent. Fluoride exhibits potent biological activity and can be extensively absorbed by the yolk sac, exerting significant effects on the development of multiple organs. This is primarily manifested as restricted nutrient utilization and elevated levels of lipid peroxidation, further leading to the accumulation of superoxide in the yolk sac, liver, and intestines. Moreover, pericardial edema exerts pressure on the brain and eye development, resulting in spinal curvature and reduced body length. Besides, acute fluoride exposure with varying concentrations has led to diverse teratogenic outcomes. A low dose of water fluoridation tends to induce abnormal development of the embryonic yolk sac, while vascular malformation is widely observed in all fluoride-treated groups. The effect of fluoride exposure on blood circulation is universally present, even in zebrafish larvae that do not exhibit obvious deformities. Their swimming behavior is also affected by water fluoridation, resulting in reduced activity and delayed reactions. In conclusion, this study provides valuable insights into the monitoring of environmental quality related to water fluoridation and disease prevention.